2019
DOI: 10.1177/2393957519863900
|View full text |Cite
|
Sign up to set email alerts
|

Measuring University Students’ Perceptions About the Role of Self-efficacy on Entrepreneurial Intentions in Cape Town

Abstract: Entrepreneurial self-efficacy is best perceived as a multidimensional variable built from individuals’ beliefs about their abilities and capabilities for tackling the challenges and nurture entrepreneurial intentions towards the establishment of a new venture. Numerous studies are unanimous about the insufficient level of entrepreneurship in South Africa, as well as its below average total entrepreneurial activity of 7.8per cent compared to all efficiency-driven economies (developed countries) which have 11.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Some schools have managed to implement and strengthen some teaching practices through the case study and business simulators, actions that eliminate obstacles to entrepreneurial intent. However, other authors point out that the main barriers to the development of creativity and that drives entrepreneurial intent are emotions and attitudes (Gomes da Costa Pedro Mares, 2016; Kalitanyi & Bbenkele, 2019). From the previous context, the following hypotheses are proposed (view Figure 1): H1.…”
Section: The Barriers Of Creativity In Entrepreneurial Intention In Tmentioning
confidence: 97%
“…Some schools have managed to implement and strengthen some teaching practices through the case study and business simulators, actions that eliminate obstacles to entrepreneurial intent. However, other authors point out that the main barriers to the development of creativity and that drives entrepreneurial intent are emotions and attitudes (Gomes da Costa Pedro Mares, 2016; Kalitanyi & Bbenkele, 2019). From the previous context, the following hypotheses are proposed (view Figure 1): H1.…”
Section: The Barriers Of Creativity In Entrepreneurial Intention In Tmentioning
confidence: 97%
“…According to a study by Kalitanyi and Bbenkele (2019), their goal was to measure awareness of the role of self-efficacy in improving the entrepreneurship intentions of college students. The study also showed that self-efficacy could influence entrepreneur success.…”
Section: H2mentioning
confidence: 99%
“…Source: adapted from Kalitanyi and Bbenkele, 2019;Natalia and Rodiah, 2019;Qiao and Huang, 2019;Huang and Zhou, 2018;Venema et al, 2015;Yurtkoru et al, 2014;Esfandiar et al, 2005.…”
Section: Figure 1 the Proposed Model Of Factors Affecting Entrepreneurial Intentionmentioning
confidence: 99%
See 2 more Smart Citations